2002
DOI: 10.1038/sj.ijo.0802166
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure in relation to relative weight at birth through childhood and youth in obese and non-obese adult men

Abstract: OBJECTIVE:To determine the influence on blood pressure of relative weight from birth through adulthood in non-obese and juvenile obese men. DESIGN: Case-cohort study of obesity in Danish men, identified at age (mean AE s.d.) 19.8 AE 1.6 y at draft board examination, who participated in at least one of two follow-up studies in adulthood (age 36.8 AE 6.7 and 47.9 AE 6.8 y at first and second followup, respectively). Birth weight and weight and height from the age of 7 -13 y were collected from school health reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
0
20
1
Order By: Relevance
“…Although Schack-Nielsen et al 24 found no direct association between low birth weight and raised blood pressure in early life among cohorts, we did find that the postnatal weight gain relative to birth weight and the current 3-year-old child's weight significantly affects the risk of having higher blood pressure early in life. It is already well known that obesity is associated with hypertension, as a result of high levels of low-density lipoproteins and low levels of high-density lipoproteins, insulin resistance and increased endothelial dysfunction and inflammation.…”
Section: Discussioncontrasting
confidence: 37%
“…Although Schack-Nielsen et al 24 found no direct association between low birth weight and raised blood pressure in early life among cohorts, we did find that the postnatal weight gain relative to birth weight and the current 3-year-old child's weight significantly affects the risk of having higher blood pressure early in life. It is already well known that obesity is associated with hypertension, as a result of high levels of low-density lipoproteins and low levels of high-density lipoproteins, insulin resistance and increased endothelial dysfunction and inflammation.…”
Section: Discussioncontrasting
confidence: 37%
“…However, this relationship was only significant when adjusted for current BMI. 18 In a study of very young children, Whincup et al 19 reported a graded inverse relationship of birth weight with BP in children aged 3 years. For each kilogram increase in birth weight, there was a decrease in SBP of 1.91 mm Hg and a decrease in DBP of 1.42 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…3 Some studies show that a statistically significant relation only exists when current weight and body mass index are adjusted for. 16 When accounting for the effect of publication bias in addition to the effect of adjusting for current weight, an update of the aforementioned meta-analysis estimated that the effect of birth weight on systolic blood pressure was reduced to a 0.4-mm Hg decrease for 1-kg increase in birth weight. 4 A criticism made of many published studies has been the failure to further adjust for potential confounders.…”
Section: Discussionmentioning
confidence: 99%